MONITORING LOCATION TRACKER UNTUK KENDARAAN BERBASIS RASPBERY Pi - Ahmad Roihan; Muhammad Sri Bintang Prasetyo; Annas Rifa'i (Journal Cerita: Creative Education of Research in Information Technology and Artificial Informatics, 2017)
Learning from the development of new technologies using the Internet as a monitoring medium, it can be ascertained that gps can be applied in various fields. These gps systems offer efficient improvements in vehicle monitoring and obtaining accurate and real time data. That with thedevelopment of new technologies that can be done that was the work-manual work using a computer that is Raspberry Pi. Data collection method is done by observation method, interview method and literature study, tool design method is done by using Fritzing application as a tool to design the system to be made and design of prototype to be built. But so far some are still local (Intranet), such as Infrared, Bluetooth and Wireless LAN. With the latest technology changing the local paradigm (Intranet) into IoT / Internet Protocol Based. In designing this tool required Raspberry Pi as Gps media as well as vehicle monitoring media using GPS, equipped with GPS module as a monitoring medium with ease. The creation of this tool may make it easy for vehicle owners to monitor vehicles remotely and provide reports in realtime.